Napovedi sprememb rabe tal v Sloveniji do leta 2012 - Petek, Franci (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
Using data from the land cadastre, we undertook an analysis of changes in land use between 1994 and 1999 and used the results to forecast changes in land use until 2012. On the basis of the linear trend of changes in the proportions of areas until 2012, we showed anticipated changes in proportions of areas according to basic land categories. The proportion of orchard should decrease the least, while the proportion of built-up area should increase the most.
Keywords: kmetijska zemljišča; raba tal; Slovenia; Slovenija; tipologija